Colombia refines NDC mitigation options and develops sustainable livestock strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Improved understanding of animal nutrition allowed policy makers and a producer organization to develop low emissions forage options in Colombia. As part of CCAFS Low Emissions Development Flagship, CIAT’s LivestockPlus project adjusted a model for digestion and metabolism for the types of livestock, feed and nutritional qualities of feed under Colombian conditions. They used the results to test forages that can provide improved nutrition, but lower emissions.